Small bowel external fistulas - Mesa, Guillermo; Cid, Alberto; Del Campo, Alberto; Mate, Miguel; Segal, Marcos; Trotschansky, José (Cirugía del Uruguay, 1978)
Intestinal fistulas cover very vast field and consequently it was decided to study only external fistulas of the snall intestine, which were deemed to be the most important.